Family Communication in Indonesian Migrant Worker's Extended Family - Hastasari, Chatia (Biokultur, 2023)
This study aims to know what the communication orientation (conversation and conformity orientation) that occurs in the migrant workers' extended family is; and what the obstacles to communication orientation that occur in the migrant workers' extended family are. The lack of job opportunities for women who only graduated from elementary school and junior high school also directly influences the number of female migrant workers working abroad every year. For female migrant workers who already have children, the role of extended families such as the presence of their parents is very important in helping their spouses (husbands) in caring for their children. Using a qualitative approach, the data were gained through the process of interviewing informants. Informants in this study were selected purposively, they were: a woman who looks after her grandchild, aged 58 years (hereinafter referred to X1) and her daughter-in-law who works as a migrant worker, aged 30 years (hereinafter referred to X2); a woman who works as a migrant worker, aged 36 years (hereinafter referred to X3) and her son, aged 18 years (hereinafter referred to X4). X1 has been living with her granddaughter for about 3 years since her daughter-in-law (X2) became a migrant worker in Taiwan in 2018. After the data from the interviews are collected, then by using a triangulation table, the data will be selected based on the needs and similarities of the interview results between informants. From the same data, it is then adjusted to the existing conceptual framework and conclusions are drawn. The results show communication orientation for conversation that occurs in migrant workers' extended family consists of discussions to decide working abroad; when grandmother told her child about her granddaughter's growth, from conversations about school choices to parenting; giving freedom to the child to be able to express and convey their wishes and make decisions based on his own considerations. Meanwhile, the conformity orientation consists of giving advice for the child to be careful in making decisions (think before acting); and behave politely and always maintain health. The advice given is usually in the form of the cultivation of discipline, rules regarding politeness, attitude and also the cultivation of values. Subsequently, the obstacles to communication orientation that occur in migrant worker extended family consist of grandparents' health and grandparents' ability to use technology. Keywords: Extended Family, grand parenting, family communication, and migrant worker